Experimental Behavior of Natural Fiber-Based Composites Used for Strengthening Masonry Structures. (19th September 2013) - Codispoti, Rosamaria; Oliveira, Daniel V.; Fangueiro, Raul; Lourenço, Paulo B.; Olivito, Renato S.
Abstract : This paper deals with the experimental characterization of the tensile behavior of fiber-based composites and flexural strength of natural fiber-reinforced polymer (NFRP) sheets externally glued on masonry bricks, in terms of load capacity and stress distribution along the bonded length. The bricks adopted for this experimentation are solid clay bricks, typically used in ancient masonry structures. Nonimpregnated and impregnated flax, hemp, jute, and sisal fibers were examined. Two types of matrices have been used, polymer matrices and mortar-based matrices. Composite materials defined as NFRP (Natural Fiber Reinforced Polymer) and NFRG (Natural Fiber Reinforced Grout) were obtained.